Telecommunication: Travel Portable Data (TPD) - Mahdzar, Mazlina; Mohd Ridzuan, Muhammad Zahid; Mohd Isa, Farah Hanani; Nazrul Fitri, Nur Hidayat; Zahilan, Nur Izzyanie Najihah; Kim, Wonyeop (Multidisciplinary Applied Research and Innovation, 2021)
Nowadays, most of the people have been facing the same problem which is the internet when they travel out from their local place. As a solution, our team members have created an idea that can solve internet problems for any individuals. Usually people have low internet coverage (line) to some places. And this sometimes will affect their intentions or desire from the usage of the internet.The idea is inspired by the ‘powerbank’ method which is often used by people to carry extra batteries for their mobile phones. But we have thought of a different idea to create a new invention that will carry internet/data (line) in the portable device or similar to powerbank. The steps are started by finding a way to transfer the internet coverage/data (line) into the device and make it portable. The size of course has a limitation (GB) and the product will surely be high in cost. This product can be a handful to a lot of people, mainly for people who committed jobs at some kind of places that are difficult to get access to the internet connection (line) such as forests, seas, rural areas and others. Advances in mobile technology are expected to create innovative experiences for consumers.